2005
DOI: 10.1089/jop.2005.21.445
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and In Vivo Assessment of Timolol-Loaded Poly(D,L-Lactide-co-Glycolide) Films for Long-Term Intraocular Pressure Lowering Effects

Abstract: Timolol-loaded poly(D,L-lactide-co-glycolide; PLGA) films were prepared for achieving the long-term intraocular pressure (IOP) lowering effect on glaucoma treatment. The physicochemical properties and in vivo effects of films were determined and characterize the delivery system. PLGA, span 20, propylene glycol (PG), and timolol base were dissolved in dichloromethane (DCM) and kept in a stainless mold; timolol films were prepared after the evaporation of DCM. Timolol disc-shape film preparation (TDF), containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…18 Polymeric systems have been used widely as implantable devices for controlled release of drugs in various organs. 19,20 In ophthalmic use, PLGA copolymers are used more commonly, for example, incorporating timolol for intraocular pressure control, 21 all-trans retinoic acid to reduce muscle adhesion in strabismus surgery, 22 cyclosporin for treatment of uveitis, 23 or 5-fluorouracil for antifibrotic effects. 24 In our study, we used PLC copolymers instead.…”
Section: Discussionmentioning
confidence: 99%
“…18 Polymeric systems have been used widely as implantable devices for controlled release of drugs in various organs. 19,20 In ophthalmic use, PLGA copolymers are used more commonly, for example, incorporating timolol for intraocular pressure control, 21 all-trans retinoic acid to reduce muscle adhesion in strabismus surgery, 22 cyclosporin for treatment of uveitis, 23 or 5-fluorouracil for antifibrotic effects. 24 In our study, we used PLC copolymers instead.…”
Section: Discussionmentioning
confidence: 99%
“…34 (Polymeric films have been used independently of contact lenses in ophthalmic drug delivery: timolol-PLGA films decrease the intraocular pressure when placed in the inferior fornix of the rabbit conjunctiva.) 35 We found that both the PLGA film and the HEMA hydrogel controlled the release of fluorescein separately and had additive effects. 28 Both fluorescein and ciprofloxacin could be released for weeks to months, with as much as a month of zeroorder kinetics.…”
Section: Entrapment Of Drug Within Contact Lensesmentioning
confidence: 77%
“…Biodegradable polymers such as Poly( D,L -lactic-co-glycolic acid) (PLGA) are commonly used as drug delivery carriers owing to many favorable characteristics such as biodegradability, good biocompatibility and favorable mechanical properties. [1][2][3][4] In recent decades, PLGA has been widely studied for localized drug delivery in treating periodontal diseases, 5,6 glaucoma 7,8 and cancer 9,10 and to coat metallic stents 11,12 and fully biodegradable stents. 13,14 Various polymeric drug delivery systems have been investigated to optimize physicochemical properties, hydrolysis rates and drug release profiles to accommodate diverse biomedical treatments.…”
Section: Introductionmentioning
confidence: 99%